Risk factors for left atrial thrombus in younger patients (aged < 65 years) with atrial fibrillation or atrial flutter: Data from the multicenter left atrial thrombus on transesophageal echocardiography (LATTEE) registry - Uziȩbło-Życzkowska, Beata; Kapłon-Cieślicka, Agnieszka; Gawałko, Monika; Budnik, Monika; Starzyk, Katarzyna; Wożakowska-Kapłon, Beata; Daniłowicz-Szymanowicz, Ludmiła; Kaufmann, Damian; Wójcik, Maciej; Błaszczyk, Robert; Hiczkiewicz, Jarosław; Łojewska, Katarzyna; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. Our aim was to assess the characteristics and to identify predictors of left atrial thrombus (LAT) in patients under age 65 with atrial fibrillation (AF) or atrial flutter (AFl). Methods. We conducted a subanalysis of a multicenter, prospective, observational study [the LATTEE registry]. Consecutive AF/AFl patients referred for cardioversion or ablation were enrolled. Results. Of the 3,109 patients included in the study, 1,276 were under age 65 (41%). Compared to non-LAT patients, those with LAT (n = 76) had higher CHA2DS2-VASc score (p < 0.001), more frequently had non-paroxysmal AF/AFl (p < 0.001), heart failure (p < 0.001), history of diabetes mellitus (p = 0.001), transient ischemic attack (p = 0.04), coronary artery disease (p = 0.02), and chronic kidney disease (p < 0.001). The LAT patients were also more often smokers (p = 0.004) and were more frequently treated with vitamin K antagonists (VKAs) (p < 0.001). Transthoracic echocardiography revealed a higher left atrial area (p < 0.001), lower left ventricular ejection fraction (LVEF) (p < 0.001), and lower value of LA appendage emptying volume in LAT than in non-LAT patients (p < 0.001). LVEF (OR 2.95; 95% CI: 1.32-6.59, p = 0.008), non-paroxysmal AF/AFl (OR 7.1; 95% CI: 2.05-24.63, p = 0.002) and treatment with VKAs (OR 4.92; 95% CI: 2.48-9.75, p < 0.001) were identified as independent predictors of LAT in younger patients. Conclusions. Our study, which focused on younger patients with AF/AFl, indicated substantial clinical and echocardiographic differences between participants with and without LAT. In the AF/AFl patients younger than age 65, the independent predictors of LAT included non-paroxysmal AF/AFl, lower LVEF, and treatment with VKAs.